Global, regional, and national burden of depressive disorders among women of childbearing age, 1990–2021: a joinpoint regression analysis for the Global Burden of Disease Study 2021 - Yang, Lulu; Luo, Yuting; Bi, Qiuhan; Luo, Binbin (Frontiers in Public Health, 2025)
BackgroundDepressive disorders, as a mental disorder, are prevalent among women, particularly women of childbearing age (WCBA). However, comprehensive epidemiological studies on this population appear to be limited globally. To investigate the longitudinal epidemiology of depressive disorders among women aged 15–49 years worldwide.MethodEstimates of annual incidence, prevalence, and disability-adjusted life years (DALYs) of depressive disorders for seven age groups (15–49 years) of women were extracted from the 2021 Global Burden of Disease Study, including 95% uncertainty intervals (UI). Age-standardized incidence rates (ASIR), age-standardized prevalence rates (ASPR), and age-standardized DALYs rates (ASDR) of depressive disorders in this population were estimated using direct age-standardization. Joinpoint regression analysis was employed to assess temporal trends in depressive disorders among this cohort from 1990 to 2021.ResultFrom 1990 to 2021, ASIR, ASPR, and ASDR of depressive disorders among WCBA increased globally. Regionally, incidence, prevalence, and DALYs rates rose in high-income areas such as North America, while a decline was observed in East Asia. Among 204 countries, Greenland, the United States of America, and Greece reported the highest ASIR, ASPR, and ASDR in 2021, with Mexico exhibiting the fastest increase. Additionally, from 2019 to 2021, most countries and regions worldwide experienced a continuous rise in the burden of depressive disorders among WCBA.ConclusionOur study provides accurate age-standardized estimates, facilitating effective comparisons across different regions. We found a sharp increase in the global burden of depressive disorders among WCBA in almost all countries and regions after 2019, highlighting an urgent need for governments to develop flexible health policies to mitigate the escalating threat of depressive disorders in this demographic.